Arbeid, arbeidere og arbeiderbevegelse på Agder 1500-2020 - Meyer, Frank (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Agder was and is an important industrial and working-class county. Wasn't it in Arendal that the Norwegian Labor Party was founded? Isn't it the case that a number of eloquent agitators, ideologues and strategists come from the South? It's not a guess that Kristiansand is new Houston? This book will help bring work, the workers and the labor movement in Agder out of oblivion. Eight authors take us through working life in Southern Norway between 1500 and 2020. The history of industrial work in Sørlandet is proud and varied: There was shipbuilding and ironworks operation, steam engines and mechanical workshops, textile industry, breweries and bakeries before 1900. Around the turn of the century, the region gained large jobs in wood processing and the electrometallurgical industry. In the 20th century, these were supplemented by many small and medium-sized businesses. And in recent times there has been another increase, with industrial work in shipbuilding and the oil industry. This anthology deals with the history of work, workers and the labor movement and also concerns challenges, conflicts and cooperation. As several of the contributions in the book show, it happened that Sørlandet's underclass took a strong stand against the authorities and employers. Labour, the workers and the labor movement in Agder not only have a past, but also a present. Two of the contributions shed light on current topics such as labor migration in and out of Agder, neoliberalism and trade union work in Agder. The chapters in the book are relevant for both researchers and lay people, not least from the labor movement, from Agder and other parts of the country.